Peluang Dan Ancaman Perdagangan Bebas Indonesia Dengan Filipina Komuditas Pertanian - Komala Sari; Muhammad Hafiedz Arrahman; Arifani Zakiah Aulianti; Nova Fahdijah Ramadani; Daspar (Jurnal Ekonomi dan Bisnis Digital, 2024)
Free trade between Indonesia and the Philippines in the agricultural sector opens up great opportunities for both countries to encourage economic growth and increase market access. This analysis aims to evaluate the potential and challenges associated with free trade between the two countries in the agricultural sector. Opportunities opened up by free trade between Indonesia and the Philippines include increased market access for agricultural products, increased investment in trade infrastructure, and exchange of technology and knowledge in the agricultural sector. Both countries can benefit from each other by increasing production and diversifying agricultural products, as well as expanding export markets. However, free trade also carries a number of threats. The imbalance in infrastructure and production capacity between the two countries is one of the main risks. The Philippines may face difficulties in competing with cheaper Indonesian agricultural products due to differences in production efficiency and labor costs. Other threats include the risk of commodity price volatility, trade policy conflicts, and the environmental impact of intensified agricultural production. By paying attention to existing opportunities and threats, free trade between Indonesia and the Philippines in agricultural commodities can be an effective instrument to support equitable and sustainable economic growth in both countries.